FYR Macedonia: Accounting and Auditing - World Bank (Washington, DC, 2013)
This report is on institutional arrangements for observing the International Accounting Standards (IAS) and International Standards on Auditing (ISA) in the Former Yugoslav Republic of Macedonia (FYR Macedonia). The current Trade Company Law requires all entities to comply with a translated 1999 volume of IAS. The Government is currently preparing a new Trade Company Law and has taken proactive steps to update the translation of IAS, which is expected to resolve existing deficiencies. In practice, compliance with IAS is not effectively enforced. Most of the financial statements reviewed by the ROSC team were of such poor quality as to preclude investors and other users from judging whether a company's securities were a sound investment; nor could the documents be relied on for other decision-making purposes. This report recommends that public interest entities be required to use IAS. It also recommends that small- and medium-size enterprises be allowed to use a reporting framework more adapted to their size. This report also recommends strengthening accounting standards enforcement mechanisms in order to enhance compliance with the law and provide investors and other users of financial statements with reliable financial reporting. Furthermore, drawing on recent international experience in developed economies and accession countries, this report recommends the establishment of a regime of delegated regulation of the auditing profession, subject to adequate oversight. The Government is currently preparing a new Audit Law that is expected to resolve existing deficiencies and be in conformity with the acquis communautaire (European Union law).